Evaluation of Occupational Accidents’ Statistics in Turkey - Ibrahim Çınar; Cem Şensöğüt (International Journal of Economic and Environment Geology)
In this work, the statistics of occupational accidents occurring in Turkey were evaluated by using SSI (Social Security Institution of Turkey) statistics between 2007-2021 and the European Union (EU) Statistical Office (EUROSTAT) data between 2011-2020. Additionally, this has been evaluated by comparing the statistics of occupational accidents in the European Union (EU) countries and Turkey, and it is observed that the measures taken to prevent fatal occupational accidents are not at a sufficient level compared to EU countries. However, the improvement in the occupational accident severity rate provided by the legal regulations made in 2012 indicates that more favorable working environments can be provided in the long run.